Prostate cancer – rehabilitation and aftercare Das Prostatakarzinom – Rehabilitation und Nachsorge - Engehausen, Dirk G.; Berger, Harald (Chirurgische Praxis, 2023)
Follow-up treatment (AHB) or rehabilitation after local therapy for prostate cancer is intended to maintain or restore physical and mental performance through appropriate measures. The AHB or rehabilitation can be carried out inpatient or daytime only on an outpatient basis, whereby different predetermined modules must be fulfilled. These modules should be aligned with the quality standards of the»Deutsche Rentenversicherung« (German Pension Insurance) and thus meet the highest quality measures. Consequences or side effects of carcinoma disease or individual therapy must be recognized at an early stage, therapies, treatments or lifestyle changes derived from it must be initiated. The focus is on the treatment and improvement of urinary incontinence, erectile dysfunction, wound healing disorders, lymphatic drainage disorders and early diagnosis of lymphoceles requiring therapy, anastomosis insufficiency and developing leg vein thrombosis. In psycho-oncological care, an understanding of the disease for the carcinoma disease should be conveyed. Care beyond the AHB or rehabilitation measure may become necessary. The restoration of participation in normal social life in private and, if necessary, in professional life are at the forefront of social work, including the initiation of benefits under the»Severely Disabled Act«. A mandatory component of successful AHB and rehabilitation treatment is the patient‘s guidance for regular urological and oncological aftercare, an individually tailored structured follow-up plan must be drawn up.
CRIS-Team Scopus Importer:2023-10-20
Keywords: aftercare; erectile dysfunction; prostate cancer; rehabilitation; urinary incontinence